2022
DOI: 10.1002/hec.4607
|View full text |Cite
|
Sign up to set email alerts
|

The impact of price promotions on sales of unhealthy food and drink products in British retail stores

Abstract: We study the health impact of food and beverage price promotion strategies—multi‐buy offers and price discounts, typically biased toward unhealthy product categories—in British consumer retail. We are the first to employ econometric models from the marketing literature to analyze the impact of price promotions with a focus on population health. Our dynamic, reduced form demand model incorporates endogenous inventory (stock piling), consumption rates imputed from repeat purchases and allows for unobserved house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In relation to food purchasing behaviours, Ditlevsen et al (2023) reported that households with low-incomes often engage in bulk purchasing to benefit from bulk-buy discounting, and Adams (2023) reported that women experiencing food insecurity made use of 'bargain bins' and coupons to maximize their purchasing power. However, in the UK, the food that is on promotion has recently been flagged for its tendency to be high in fat, sugar and salt (HFSS), which has been found to contribute to excess food intake (Watt et al, 2023). Households with low-incomes also report engaging in financial budgeting as this allows households to manage limited resources effectively (Douglas, 2023;Power et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to food purchasing behaviours, Ditlevsen et al (2023) reported that households with low-incomes often engage in bulk purchasing to benefit from bulk-buy discounting, and Adams (2023) reported that women experiencing food insecurity made use of 'bargain bins' and coupons to maximize their purchasing power. However, in the UK, the food that is on promotion has recently been flagged for its tendency to be high in fat, sugar and salt (HFSS), which has been found to contribute to excess food intake (Watt et al, 2023). Households with low-incomes also report engaging in financial budgeting as this allows households to manage limited resources effectively (Douglas, 2023;Power et al, 2018).…”
Section: Introductionmentioning
confidence: 99%